THE INFLUENCE OF PHYLOGENY TREE-ASSISTED TPS OF INVERTEBRATA MATERIALS TOWARDS STUDENTS’ COGNITIVE LEARNING RESULTS AND CRITICAL THINKING ABILITY - Wulandari, Yulia Hafsah; Supriyanto, Supriyanto; Priyono, Bambang (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Abstract ___________________________________________________________________ Efforts to improve the critical thinking skills of students of SMAN 1 Bae Kudus in meeting the rules of Graduate Competency Standards required communicative learning model in order to stimulate ideas and mental namely models TPS (Think Pair Share) aided phylogeny tree to help students more easily understand the material invertebrates. This study aims to determine the effect of phylogeny tree-aided model of TPS material invertebrates on the cognitive learning and critical thinking skills activities. The research objectives include the class X second semester of the 2015/2016 academic year. Class sample is X MIPA 1 (experimental class) and X MIPA 4 (control class) with a convenience sampling technique. The study design using posttest only controls group design. The results of descriptive teacher responses indicate TPS models make the discussion more effective and more active for student. Students give feedback as much as 75.0-93.1% with good-excellent category on the positive statement. Activity of students in the experimental class as much as 78% of students are very active, the cognitive learning critical thinking high as 84% of students are very critical with classical completeness percentage of 90.6%. Researches by applying the model TPS-aided phylogeny tree have positive effect on the cognitive learning and critical thinking skills activity of students. Model TPS-aided phylogeny tree is effective and can be applied in learning activities invertebrate material.